Cadmium-Induced Proteinuria: Mechanistic Insights from Dose–Effect Analyses - Satarug, Soisungwan; Vesey, David A.; Gobe, Glenda C. (International journal of molecular sciences, 2023)
Cadmium (Cd) is a toxic metal that accumulates in kidneys, especially in the proximal tubular epithelial cells, where virtually all proteins in the glomerular ultrafiltrate are reabsorbed. Here, we analyzed archived data on the estimated glomerular filtration rate (eGFR) and excretion rates of Cd (ECd), total protein (EProt), albumin (Ealb), β2-microglobulin (Eβ2M), and α1-microglobulin (Eα1M), which were recorded for residents of a Cd contamination area and a low-exposure control area of Thailand. Excretion of Cd and all proteins were normalized to creatinine clearance (Ccr) as ECd/Ccr and EProt/Ccr to correct for differences among subjects in the number of surviving nephrons. Low eGFR was defined as eGFR ≤ 60 mL/min/1.73 m2, while proteinuria was indicted by EPro/Ccr ≥ 20 mg/L of filtrate. EProt/Ccr varied directly with ECd/Ccr (β = 0.263, p < 0.001) and age (β = 0.252, p < 0.001). In contrast, eGFR values were inversely associated with ECd/Ccr (β = −0.266, p < 0.001) and age (β = −0.558, p < 0.001). At ECd/Ccr > 8.28 ng/L of filtrate, the prevalence odds ratios for proteinuria and low eGFR were increased 4.6- and 5.1-fold, respectively (p < 0.001 for both parameters). Thus, the eGFR and tubular protein retrieval were both simultaneously diminished by Cd exposure. Of interest, ECd/Ccr was more closely correlated with EProt/Ccr (r = 0.507), Eβ2M (r = 0.430), and Eα1M/Ccr (r = 0.364) than with EAlb/Ccr (r = 0.152). These data suggest that Cd may differentially reduce the ability of tubular epithelial cells to reclaim proteins, resulting in preferential reabsorption of albumin.